PENGARUH PEMBERIAN KARBOL FUCHSIN DAN PEMANASAN SPUTUM SEBELUM PEMBUATAN SEDIAAN TERHADAP HASIL PEWARNAAN BTA - Mega Mirawati; Estu Lestari (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. This disease is a health problem in the community. Minimal checks that need to be done to confirm pulmonary tuberculosis diagnostics are smear examinations. ZiehlNelseen method is an inspection method recommended by WHO. Sputum used to make preparations is a mucopurulent sputum. This can lead to infected laboratory workers if inhaled droplets containing Mycobacterium tuberculosis. This study aims to determine the effect of fuchsin carbolic acid and sputum heating before the preparation of the smear result. Temperature used 60oC, 70oC, 80oC and 90oC and control is sputum staining with Ziehl Neelsen method. The samples used positive smear sputum. The experimental research design and data were analyzed with Kruskal Wallistest. The research was conducted at the Bacteriology Laboratory of Medical Laboratory Technology Poltekkes Kemenkes Jakarta III in February to October 2016. The result of statistical test showed p> 0,301 which means there was no significant difference between the dyeing result by using sputum which has been given carbolic fuchsin and heating before the preparation with the result staining method ZiehlNeelsen. The conclusion of this method can coloring Mycobacterium tuberculosis bacteria.